Cross-cultural validation and measurement invariance of anxiety and depression symptoms: A study of the Brief Symptom Inventory (BSI) in 42 countries - Quintana, Gonzalo R; Ponce, Fernando P; Escudero-Pastén, Javier I; Santibáñez-Palma, Juan F; Nagy, Léna; Koós, Mónika; Kraus, Shane W; Demetrovics, Zsolt; Potenza, Marc N; Ballester-Arnal, Rafael; Batthyány, Dominik; Bergeron, Sophie; et al. (Elsevier BV, 2024)
Depression and anxiety are among the most prevalent mental health issues experienced worldwide. However, whereas cross-cultural studies utilize psychometrically valid and reliable scales, fewer can meaningfully compare these conditions across different groups. To address this gap, the current study aimed to psychometrically assess the Brief Symptomatology Index (BSI) in 42 countries.